2019
DOI: 10.29252/ijpd.15.1.93
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the antibacterial effect of nanosilver and chlorhexidine mouthwash on Streptococcus mutans (invitro)

Abstract: Comparison of the antibacterial effect of nanosilver and chlorhexidine mouthwash on Streptococcus mutans (invitro)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…NPAg are also used in dental appliances. It has been shown that a resin composite incorporated into materials containing NPAg exerts a long-lasting inhibitory effect against Streptococcus mutans (Faiyaz et al 2019;Rabani et al 2019;Yoshida et al 1999). It has also been shown that a resin composite containing fillers implanted with silver ions releases antimicrobial silver ions on oral streptococci (Corrêa et al 2015).…”
Section: Disinfecting Activity Ag/tio2mentioning
confidence: 99%
“…NPAg are also used in dental appliances. It has been shown that a resin composite incorporated into materials containing NPAg exerts a long-lasting inhibitory effect against Streptococcus mutans (Faiyaz et al 2019;Rabani et al 2019;Yoshida et al 1999). It has also been shown that a resin composite containing fillers implanted with silver ions releases antimicrobial silver ions on oral streptococci (Corrêa et al 2015).…”
Section: Disinfecting Activity Ag/tio2mentioning
confidence: 99%
“…One of the advantages of chlorhexidine is its ability to adhere to oral tissues, allowing it to release slowly and provide antimicrobial effects over a certain period of time. The mechanism of action of chlorhexidine is adherence to the bacterial cell wall [ 6 ]. Due to its property of substantivity, chlorhexidine adsorbs to tooth surfaces destabilizes bacterial cell walls and interferes with cellular osmosis, leading to lysis of bacterial cells.…”
Section: Introductionmentioning
confidence: 99%
“…Long-term use of chlorhexidine can result in discoloration of teeth, restorations, oral mucosa, and tongue dorsum. In addition, bad taste, xerostomia, and detrimental effects of oral microflora is other disadvantages of chlorhexidine [ 6 ]. Therefore, researchers have sought other antimicrobial agents for using as mouthwash [ 6 , 9 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation